Potret Fenomena Tahfiz Online di Indonesia - Heriyanto, Heriyanto (SUHUF, 2021)
This study questions the phenomenon of the trend of memorizing the Qur’an through online technological media, either by using social media, interactive websites or Android applications. This research uses the living Qur’an study model, whose data are taken through the observation from the internet, interviews and literature searches from various available sources. The study is expected to be able to explore emergingpatterns, networks and methods used, so that the online tahfiz phenomenon can be well translated. The results of the study indicate the shift in sanad (chained) authority in online tahfiz practice. The talaqqi process in traditional tahfiz education is transformed into talaqqi-virtual. Teachers and students do not have to meet directly to ensure the authenticity of the Qur’an being memorized. The tradition of memorizingthe Qur’an through the internet has created a new reality in the context of the Living Qur’an which the author calls the e-living Qur’an. If living Qur’an examines communities that live in the midst of society in the real world, then e-living Qur’an is a model of Quranic studies that targets virtual communities through online communities.